Heinrich Scholz und die religiöse Musik - Strobach, Niko (NTT, 2025)
The present paper provides a first survey of the traces that religious music left in the writings of Heinrich Scholz. It is shown that Scholz used to allude to European classical music, in particular church music, throughout his life as a means of communication, and that a small early monograph by Scholz on church music deserves to be taken seriously as a text on the aesthetics of music, in which Scholz tries to combine Eduard Hanslick’s philosophy of music with Friedrich Schleiermacher’s concept of religion.